A CRITICAL DISCOURSE ANALYSIS OF CAR ADVERTISEMENTS IN TELEVISION - Sakia Hermila Tantri; Veronika Unun Pratiwi; Imroatus Solikhah; Sari Handayani (Universitas Veteran Bangun Nusantara, 2019)
This research was conducted to find out realities that showed on discourse of car advertisements in television based on the criticaldiscourse analysis theory by Guy Cook and to know the purposes that are showed in car advertisements on television.This research used the Critical Discourse Analysis based on Guy Cook’s theory. It is a descriptive qualitative research in conductingthe research. The data of this research are 21 car advertisements that are in four commercial televisions, such as metro TV, Trans 7, MNC TV, andRCTI. The data are taken from spoken text, written text, and also expression of the advertisement models. The researcher also uses respondents toanswer the questionnaire. This questionnaire is used to answer second problem statement that is the purposes that are showed in car advertisementsin television.Based on the analysis, eight elements of Guy Cook’s theory in Critical Discourse Analysis are substance, music and pictures,paralanguage, situation, co-text, intertext, participant, and function. It can be concluded that 100% of 21 car advertisements contains substance,music and pictures, paralanguage, situation, participant, and function. From 21 car advertisement, there are two car advertisements that contain cotext.So the percentage is 9, 52%. Then, only Daihatsu (Man. City vs Daihatsu Team version) that didn’t contained in intertext. So, the percentageof the car advertisements that contain intertext is 90, 47%.Based on the questionnaires which were distributed to the 15 people in all segments, the purposes of car advertisements are to influencethe people to choose the product based on its strengths. Because of advertisement, the power of interest also appears by the costumer to buy thisproduct.Based on the findings, it is suggested that the teacher have to conduct some research about Critical Discourse Analysis in other subjects.For the student, it is expected they can explore Critical Discourse Analysis in other theories, such as theory from Roger Fowler and friends,Theo Van Leeuwenn, Sara Mills, Van Dijk, and Norman Fairclough. For other researchers, it suggested to conduct a research in other subject ofadvertisement and other theories of Critical Discourse Analysis. Besides, it is also suggested to the other researcher to analyze the data which aretaken from the different data sources, such as advertisements and articles in magazines, newspaper, and others.